Childlessness and sibling positioning in upward intergenerational support: Insights from Singapore - KIM, Dahye (Institutional Knowledge at Singapore Management University, 2024)
Objective: This brief report aims to explore the role of child-lessness and its interaction with sibling positioning (i.e., birth order and gender) in upward intergenerational support within the context of Asian familial and patrilineal values. Background: Despite the increasing rates of childlessness in Asia, little is known about how childless individuals deviate from or adhere to the patrilineal gendered practices of supporting their older parents. Singapore, a rapidly aging nation that emphasises Confucian familism values and patrilineal practices in guiding its welfare policies, provides an ideal setting for this research investigation. Method: We analysed a sample of 475 Singaporeans aged 50 and above with at least one living parent from a recent nationwide survey. We utilised multivariate regressions to examine the associations between childlessness and various types of upward intergenerational support, with further heterogeneity analyses based on sibling positioning. Results: The traditional patrilineal pattern of first-born sons providing the most financial transfers to aging parents was found among non-childless individuals. In contrast, all childless individuals, regardless of their birth order and gender, played a significant role in providing intergenerational support, particularly in instrumental and associational support, as well as maintaining geographical proximity to their parents. Conclusion: Childless individuals in Singapore were found to shoulder the primary responsibility for supporting parents, thus upholding the values of filial piety and familism. Results further suggest that the rising prevalence of childlessness may contribute to the erosion of patrilineal norms in upward intergenerational support in Asia.